(untitled) (Comparative Professional Pedagogy, 2024)
The article presents a comparative analysis of domestic and foreign approaches to the development of social workers’ professional competence. It examines the key components of professional training, including theoretical knowledge, practical skills, communication abilities, and ethical orientation. The findings indicate that domestic practices focus on traditional educational models with limited access to innovative technologies, while foreign systems are characterized by interdisciplinarity and extensive use of modern teaching methods and technologies. Particular attention is given to the integration of innovations in the educational process, which play a pivotal role in the preparation of social workers abroad. Foreign approaches include active collaboration with professional associations, the use of digital platforms for remote learning, and the introduction of simulations for practical training. These methods ensure systemic and comprehensive knowledge, as well as adaptability to contemporary societal challenges. A significant aspect of the research is the role of professional organizations in ensuring continuous professional development for social workers. The article emphasizes that such associations promote experience sharing, establish professional standards, and foster the development of innovative practices in social work. The foreign experience is highlighted as a valuable resource for enhancing the domestic training system, particularly through the creation of similar professional organizations in Ukraine. The article provides recommendations for improving the training system for social workers in Ukraine, including the implementation of innovative technologies, the expansion of practical training opportunities, and increased collaboration with international organizations. It stresses the importance of adapting foreign practices while considering the unique context of Ukraine. The findings underline the necessity of a comprehensive approach to developing professional competence of social workers. Future research could focus on the practical implementation of these recommendations and evaluation of their effectiveness in improving the quality of social work in Ukraine.